PENENTUAN VISKOSITAS MOONEY DARI KARET DENGAN BAHAN PENGISI ARANG - Rudi Munzirwan Siregar (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract Research on the Determination of Viscosity Money From Rubber by Fillers Charcoal has been done. Each latex was added into the coconut shell charcoal  ( particle size 80 mesh ) were 36 , 38 , 40 , 42 , and 44 grams. Then the latex is coagulated with formic acid in pH 4.7. Formic acid is used as a control for the rubber crumple without the addition of coconut shell. Research carried out by measuring the quality of rubber Money Viscosity. From the results of research it turns out that the value of the viscosity of the money obtained by the addition of charcoal to the rubber in the latex is 72.5 ; 74 ; 75.5 ; 77 ; and 75. It can be seen that the value of the best rubber Mooney viscosity of 75 , so the rubber with medium Mooney viscosity value  able to provide a meeting point between the energy efficient with superior physical properties. Keywords : Rubber , Viscosity Money , Coconut Shell Charcoal